Real exchange rates and sectoral productivity in the Eurozone (working paper) - Berka, M; Devereux, MB; Engel, C (NBER, 2014)
We investigate the link between real exchange rates and sectoral TFP for Eurozone countries. We show that real exchange rate variation, both cross-country and time series, closely accords with an amended Balassa-Samuelson interpretation, incorporating sectoral productivity shocks and a labor market wedge. We construct a DSGE model to generate a cross-section and time series of real exchange rates to compare to data.Estimates from simulated regressions are very similar to estimates for Eurozone data. Our findings contrast with previous studies that have found little relationship between productivity and real exchange rates among high-income countries that have floating nominal exchange rates.
Keywords: Balassa-Samuelson; Real Exchange Rates; Eurozone; Total Factor Productivity; Labor Wedge; Unit Labor Cost